Comparison of Surface Characteristics of Medical-grade 316L Stainless Steel Processed by Sand-blasting, Slag Ball-blasting and Shot-blasting Treatments - Budi Arifvianto; Muslim Mahardika; Urip Agus Salim; Suyitno Suyitno (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
In this research, a comparative study was carried out to examine the surface characteristics of medical-grade 316L stainless steel after blasting treatments by using angular silica particles, spherical slag balls and spherical metallic shot. The surface roughness, morphology, elemental composition and microhardness distribution of the stainless steel were determined and the possible mechanisms in the evolution of the surface characteristics of the steel exposed to the blasting treatments were established. The results showed that all the blasting treatments conducted in this research increased the roughness and hardness of the steel surface. In this case, the roughest stainless steel surface was achieved by the slag ball-blasting treatment, but the stainless steel with the hardest surface and the thickest hard subsurface layer was obtained by the shot-blasting treatment. On the basis of the findings in this research it can be concluded that the physical properties and surface morphology of particles or shot used in the blasting treatment are critical parameters in determining the surface characteristics of blasted stainless steel.